PROBLEMATIKA PEMENUHAN HAK MENYAMPAIKAN PENDAPAT DAN PELANGGARAN TERHADAP HAK ATAS KESEHATAN DI INDONESIA - Tat Marlina; Duwi Handoko (Ensiklopedia of Journal, 2021)
The purpose of this paper is to find out the problem of fulfilling the right to express opinions and violations of the right to health in Indonesia. This type of research is normative legal research specifically discussing human rights in the field of expressing opinions and rights to health. Data analysis in this study was carried out systematically based on the research problems described qualitatively. In relation to expressing opinions in public, such as demonstrations or demonstrations with many participants, restrictions on freedom are usually associated with "public order" or public orders. The most difficult is how to provide a balance between freedom and public order. Demonstrations by a number of doctors certainly have an impact on patient care, which in principle has harmed the public interest. In addition, the demonstration by blocking the road body certainly hurts the public interest, namely the interests of all road users. Based on the results of Komnas HAM's investigation, at least 15 types of human rights violations were affected by Lapindo mudflow victims. The problem when it is associated with the right to health is in the form of: not a few refugees whose health is disrupted resulting in people falling ill and some dying due to the absence of a proper environment for displaced people; and gas contaminated air and clean water facilities that are damaged are not handled properly by the government.